Fixed-outline floorplanning: enabling hierarchical design - Adya, S.N.; Markov, I.L. (IEEE transactions on very large scale integration (VLSI) systems, 2003)
Classical floorplanning minimizes a linear combination of area and wirelength. When simulated annealing is used, e.g., with the sequence pair representation, the typical choice of moves is fairly straightforward. In this paper, we study the fixed-outline floorplan formulation that is more relevant to hierarchical design style and is justified for very large ASICs and SoCs. We empirically show that instances of the fixed-outline floorplan problem are significantly harder than related instances of classical floorplan problems. We suggest new objective functions to drive simulated annealing and new types of moves that better guide local search in the new context. Wirelength improvements and optimization of aspect ratios of soft blocks are explicitly addressed by these techniques. Our proposed moves are based on the notion of floorplan slack. The proposed slack computation can be implemented with all existing algorithms to evaluate sequence pairs, of which we use the simplest, yet semantically indistinguishable from the fastest reported . A similar slack computation is possible with many other floorplan representations. In all cases the computation time approximately doubles. Our empirical evaluation is based on a new floorplanner implementation Parquet-1 that can operate in both outline-free and fixed-outline modes. We use Parquet-1 to floorplan a design, with approximately 32000 cells, in 37 min using a top-down, hierarchical paradigm.